Association of traits in Ethiopian fenugreek (Trigonella foenum-graecum L.) genotypes regarding to seed yield by using phenotypic data - Yimam ALI ABTEW; Alemu ABATE (Acta Agriculturae Slovenica)
Shortage of information on association of traits is one of the problems in fenugreek productivity. Field experiment was implemented at Jamma district of South Wollo Administrative Zone of Amhara National Regional State, in 2018/19 main rainy season to examine the nature and extent of correlation, direct and indirect effects among yield and yield related traits. Sixty-two nationally collected fenugreek genotypes along with standard and local checks were evaluated in simple lattice design. Seed yield plot-1 was significantly and positively correlated to biomass yield-1 (r = 0.5) and harvest index (r = 0.6***) at genotypic level. Seed yield was also significantly and positively correlated with harvesting index (r = 0.6***) and weakly and negatively (r = -0.01) correlated to biomass yield at phenotypic level. Path coefficient analysis revealed that biomass (0.951), harvesting index (0.283) and pod length (-0.163) had contributed the maximum positive and negative direct effect on seed yield respectively, at phenotypic level. At genotypic level biomass yield ha-1 (0.816) and harvesting index (0.930) had contributed strong positive direct effect and plant height (-0.004) had revealed weak negative direct effect.